Pembelajaran Biologi Cacing Nyale Melalui Pendekatan Saintifik Berbantukan Video Pembelajaran untuk Meningkatkan Kemampuan Berfikir Kritis Siswa SMAN di Kota Mataram - Baiq Sri Handayani; Imam Bachtiar; Syamsul Bahri; Lalu Japa (Postgraduate, University of Mataram, 2022)
The research was carried out with the aim of knowing the effectiveness of the video-assisted scientific approach on students' critical thinking skills. The study used a quasi-experimental method. The research was carried out on high school students in the city of Mataram with a total sample of 323 as the research sample. Data Inferential analysis with Analysis of Covariance (ANACOVA) followed by Least Significance Difference (LSD), was used to test the research hypothesis. The results showed that the learning approach had a significant effect on learning activities with an F hit value of 60.37. The scientific approach is not significantly different from the video-assisted scientific approach, but is significantly different from the conventional approach with a mean value of 62.17 for video-assisted scientific approaches and an average of 64.69 and a conventional approach of 47.48. The video-assisted scientific approach improves students' critical thinking skills.